Primary Immune Deficiencies – Principles of Care - Chapel, Helen; Prevot, Johan; Gaspar, Hubert Bobby; Español, Teresa; Bonilla, Francisco A.; Solis, Leire; Drabwell, Josina; , The Editorial Board for Working Party on Principles of Care at IPOPI (Frontiers in Immunology, 2014)
Primary Immune Deficiencies (PIDs) are a growing group of over 230 different disorders caused by ineffective, absent or an increasing number of gain of function mutations in immune components (mainly cells and proteins). Once recognised, these rare disorders are treatable and in some cases curable. Otherwise untreated PIDs are often chronic, serious or even fatal. The diagnosis of PIDs can be difficult due to lack of awareness and facilities for diagnosis, and management of PIDs is complex. This document was prepared by a worldwide multi-disciplinary team of specialists; it aims to set out comprehensive principles of care for PIDs. These include the role of specialised centres, the importance of registries, the need for multinational research, the role of patient organisations, management and treatment options, the requirement for sustained access to all treatments including immunoglobulin (Ig) therapies and HSCT, important considerations for developing countries and suggestions for implementation. A range of healthcare policies and services have to be put into place by government agencies and healthcare providers, to ensure that PID patients world-wide have access to appropriate and sustainable medical and support services.